Language Learning Beyond the Textbooks: A Reflection on Teaching Language to Children - Manwal, Kalpana (THE PRIMARY TEACHER, 2018)
vormal education begins with the main focus on three aspects—Numeracy, Literacy and Environment. Out of the three, language is the first thing that a child becomes aware of and starts using at an early age. Making sense of numbers and understanding the relationship with the environment is introduced later, but language is present right from the beginning. This paper details out the importance of learning beyond the textbooks and understanding language as a part of their everyday usage. Language is the most intrinsic part of human existence, and hence, it is best learned in a asocial environment